(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
The objective of this work is to understand the dynamics and operation schemes of global knowledge networks, specifically from the case of the Colombia Chapter of the Global MX Network, reflecting on its role as a space for interaction, exchange and circulation of experiences, as well as the execution of projects of social benefit that contribute to the construction of the globalization of solidarity. The methodology used was qualitative and the semi-structured interview was used to collect the information. Among the main findings, it was identified that the actions promoted by the members of this Chapter exceed their purpose of public policy of linking and circulation of knowledge, to the extent that their scope is extended towards a social, human and social benefit sense.